2007
DOI: 10.1093/glycob/cwm017
|View full text |Cite
|
Sign up to set email alerts
|

Selective clearance of glycoforms of a complex glycoprotein pharmaceutical caused by terminal N-acetylglucosamine is similar in humans and cynomolgus monkeys

Abstract: To understand how the carbohydrate moieties of a recombinant glycoprotein affected its pharmacokinetic (PK) properties, the glycan distribution was directly assessed from serial blood samples taken during PK studies in cynomolgus monkeys and humans. The protein studied was an immunoadhesin (lenercept), containing an Fc domain from human immunoglobulin G (IgG-1) and two copies of the extensively glycosylated extra cellular domain of tumor necrosis factor receptor p55. The protein was recovered in pure form usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 34 publications
2
67
0
Order By: Relevance
“…Low abundant glycopeptides detected at m/z 2802.13 and 2640.11 from CEM cells after transfection with Herceptin/LipA (supplemental Fig. S3a) have been previously observed in the study of Fc domain of immunoadhesine affected by drugs (40).…”
Section: Discussionsupporting
confidence: 59%
“…Low abundant glycopeptides detected at m/z 2802.13 and 2640.11 from CEM cells after transfection with Herceptin/LipA (supplemental Fig. S3a) have been previously observed in the study of Fc domain of immunoadhesine affected by drugs (40).…”
Section: Discussionsupporting
confidence: 59%
“…Although a 1.5-to 3-fold lower half-life in serum was observed for oligomannose containing antibodies compared to the control antibody in these studies, the 4.6-day (Kanda et al, 2007) and 2.8-to 4-day (Wright et al, 1994(Wright et al, , 1998 half-lives of the oligomannose containing antibodies are still much longer than many non-antibody like glycoproteins with oligomannose residues, which have half-lives of a few minutes (Kogerlberg et al, 2007;Sareneva et al, 1993;Van Patten et al, 2007). The difference in half-lives between antibody and nonantibody like glycoprotein with oligomannose residues prompted us to compare their binding to mannose receptor (Jones et al, 2007;Su et al, 2005). Interestingly, the results from the current study show much less binding of an antibody with Man9 glycans to mannose receptor compared (Van Patten et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…However, the impact of Fc glycosylation on antibody clearance is not fully established. Recently, it was reported that the distribution of terminal GlcNAc-containing versus terminal galactose-containing glycans in the Fc domain of antibody or Fc fusion protein was not significantly altered when the protein was recovered at different time points in serum after injection, suggesting these glycans are sequestered in the interior of the Fc (Huang et al, 2006;Jones et al, 2007). It is known that mannose receptor binds to GlcNAc terminated complex-type as well as oligomannose-type glycans.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of additional N-glycosylation motifs into the peptide sequence of erythropoietin can result in increased serum half-lives (6). Glycosylation also dictates the serum half-life of glycoprotein drugs, capable of neonatal Fc-receptor-mediated recycling, as shown for the systemic TNF inhibitor Lenercept, a fusion protein consisting of an IgG1 Fc portion and the extracellular p55 TNF receptor domain (7). However, quantitative studies investigating the impact of protein glycosylation on disease-homing properties of therapeutic proteins are rare.…”
mentioning
confidence: 99%